Peningkatan Kemampuan Membaca Pemahaman Menggunakan Model Discovery Learning pada Peserta Didik Kelas IV SDN 20 Indarung Kota Padang - Nafizah, Khairiatun; Sukma, Elfia; Muhammadi, Muhammadi; Azima, Nana Fauzana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the improvement of students' reading comprehension skills through the application of the Discovery Learning model to the fourth-grade students of SDN 20 Indarung in Padang City. This type of research is Classroom Action Research (CAR) with qualitative and quantitative approaches, which is conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study are the teacher and the students in grade IV SDN 20 Indarung, totaling 30 people, consisting of 16 female students and 14 male students. The research results indicate that the teaching module experienced an improvement from cycle I with an average percentage of 85.41% categorized as good (B) to 91.66% rated as very good (SB) in cycle II. The implementation of learning through the observable aspects of the teacher improved from cycle I with an average percentage of 82.81% categorized as good (B) to 90.62% rated as very good (SB) in cycle II. Meanwhile, the observable aspect of the students improved from cycle I with an average percentage of 81.25% categorized as good (B) to 87.5% rated as good (B) in cycle II. The results of students' reading comprehension skills using the Discovery Learning model have increased from cycle I with an average percentage of 74.45% with a sufficient predicate (C) to 89.01% good (B) in cycle II. With this in mind, the Discovery Learning model can improve the reading comprehension skills of students in class IV SDN 20 Indarung Kota Padang.